Factors influencing students' attitude towards HIV/AIDS in a public university, Malaysia - Rahnama, Rozina; Gyanchand Rampal, Lekhraj Rampal; Lye, Munn Sann; Abdul Rahman, Hejar (Canadian Center of Science and Education, 2011)
Acquired Immunodeficiency Syndrome has remained one of the priority global public health challenges. The aim of this cross-sectional study was to determine the attitudes related to HIV/AIDS among students in a public university in Malaysia. The students were selected based on a two-stage probability proportionate to size random sampling method. Data was analyzed using SPSS version 17. Out of the 1773 respondents, 57.3 % were female and the mean age was 22.5 years. The results showed that only 19.5 % stated that they will inform their partners or family if diagnosed positive for HIV infection and 43 % were willing to care for an HIV infected person in their own house. The overall mean attitude score was 24.1. Knowledge was significantly associated with the attitude towards HIV/AIDS among students. However, age, educational level, marital status, place of residence was not associated with the attitude towards HIV/AIDS among students.